Polymers against Microorganisms On the Race to Efficient Antimicrobial Materials - Rodríguez-Hernández, Juan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides an introductory and general overview of advances in polymers towards their employment as antimicrobial materials. The author describes current approaches for avoiding microbial contamination, toward macro-molecular antibiotics, and prevention of antibiotic-resistant bacteria by use of polymers. He establishes the remaining issues and analyzes existing methodologies for treating bacterial infections and for preparing antimicrobial materials. • Offers a complete and brief overview of different strategies for preparation of antimicrobial materials; • Places contamination problems in the context of what polymers can offer for remediation using different alternatives to remove and prevent bacterial infections; • Describes how polymers with antimicrobial activity can interact in various ways.
Polymers Against Microorganisms -- Bacterial infections: few concepts -- Chemical approaches to prepare antimicrobial polymers -- Nano-micro polymeric structures with antimicrobial activity in solution -- Antimicrobial/antifouling surfaces obtained by surface modification -- Nano/microstructured Antibacterial Surfaces -- Antimicrobial fibers and fabrics obtained by electro/melt spinning -- Antimicrobial hydrogels -- Antibacterial polymeric membranes -- Environmental and safety issues -- Applications and current status of antimicrobial polymers.
Keywords: Biomaterials; Polymers; Medical microbiology; Biomaterials; Polymers; Medical Microbiology